2008
DOI: 10.1128/iai.00379-07
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity in Macrophages Infected with Rough Brucella Mutants Is Type IV Secretion System Dependent

Abstract: Smooth Brucella spp. inhibit macrophage apoptosis, whereas rough Brucella mutants induce macrophage oncotic and necrotic cell death. However, the mechanisms and genes responsible for Brucella cytotoxicity have not been identified. In the current study, a random mutagenesis approach was used to create a mutant bank consisting of 11,354 mutants by mariner transposon mutagenesis using Brucella melitensis rough mutant 16M⌬ manBA as the parental strain. Subsequent screening identified 56 mutants (0.49% of the mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
45
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 47 publications
5
45
1
Order By: Relevance
“…In agreement with the observations reported for S Brucella strains (16,17,42,44), the T4SS is also essential for the multiplication and survival of R virulent B. ovis strain PA in mice and in J774.A1 macrophages (Fig. 4 and 5).…”
Section: Figsupporting
confidence: 80%
See 3 more Smart Citations
“…In agreement with the observations reported for S Brucella strains (16,17,42,44), the T4SS is also essential for the multiplication and survival of R virulent B. ovis strain PA in mice and in J774.A1 macrophages (Fig. 4 and 5).…”
Section: Figsupporting
confidence: 80%
“…However, these results differ from those published for an R mutant (⌬manBA) of S B. melitensis 16M. The intracellular counts of that mutant decreased over time in J774.A1 murine macrophages, whereas the double mutant 16M ⌬manBA ⌬virB2 showed an unexpected resistance to killing by macrophages in the absence of T4SS that was coupled to a loss of the cytotoxic effect of the single ⌬manBA mutant (44). In contrast, the cytotoxic effect for macrophages-which has also been observed in R mutants derived from S B. abortus (43)-was not evidenced with B. ovis PA or the mutant strains obtained in this work (data not shown).…”
Section: Figcontrasting
confidence: 56%
See 2 more Smart Citations
“…However, the mechanisms behind attenuated infection by the rough mutant have not been deciphered completely. In a previous study, artificial Brucella rough mutants were found to be cytopathic for macrophages and dependent on the type 4 secretion system (T4SS) (36,37), but the effectors delivered by the T4SS are still unknown.…”
Section: Discussionmentioning
confidence: 99%